Coyote lost and found eaudiobook - Gemeinhart, Dan (Coyote Sunrise, 2024)
"Khristine Hvam's narration is as heartfelt as the story of 12-year-old Coyote Sunrise...both the story and Hvam's distinctive narration will linger in listeners' minds" — AudioFile on The Remarkable Journey of Coyote Sunrise , an Earphones Award winner From #1 New York Times -bestselling author Dan Gemeinhart comes a standalone companion to the critically-acclaimed The Remarkable Journey of Coyote Sunrise about a father and daughter who venture on a moving, uplifting, and rollicking cross-country road trip. It's been almost a year since Coyote and her dad left the road behind and settled down in a small Oregon town. . . time spent grieving the loss of her mom and sisters and trying to fit in at school. But just as life is becoming a new version of normal, Coyote discovers a box containing her mom's ashes. And she thinks she might finally be ready to say goodbye. So Coyote and her dad gear up for an epic cross-country road trip to scatter the ashes at her mom's chosen resting place. The only problem? Coyote has no idea where that resting place is—and the secret's hidden in a book that Coyote mistakenly sold last year, somewhere in the country. Now, it's up to Coyote to track down the treasured book . . . without her dad ever finding out that it's lost. It's time to fire up their trusty bus, Yager, pick up some old friends, discover some new ones, and hit the road on another unforgettable adventure. "Your heart needs this joyful miracle of a book." —Katherine Applegate, acclaimed author of The One and Only Ivan and Wishtree , on The Remarkable Journey of Coyote Sunrise A Macmillan Audio production from Henry Holt & Company.